2016
DOI: 10.3389/fmicb.2016.01507
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of High Pressure CO2 and Nisin on Inactivation of Bacillus subtilis Spores in Aqueous Solutions

Abstract: The inactivation effects of high pressure CO2 + nisin (simultaneous treatment of HPCD and nisin, HPCD + nisin), HPCD→nisin (HPCD was followed by nisin), and nisin→HPCD (nisin was followed by HPCD) treatments on Bacillus subtilis spores in aqueous solutions were compared. The spores were treated by HPCD at 6.5 or 20 MPa, 84–86°C and 0–30 min, and the concentration of nisin was 0.02%. Treated spores were examined for the viability, the permeability of inner membrane (IM) using flow cytometry method and pyridine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The subpopulation of ungerminated spores sensitized to nisin could have been modified by HP in a way that promotes access of nisin to the IM. Rao et al (2016) found similar results on B. subtilis spores treated by HP CO 2 (HPCD) combined with nisin. The authors suggest that HPCD promotes the penetration of nisin into the spores by damaging their coat and cortex.…”
Section: Discussionsupporting
confidence: 56%
“…The subpopulation of ungerminated spores sensitized to nisin could have been modified by HP in a way that promotes access of nisin to the IM. Rao et al (2016) found similar results on B. subtilis spores treated by HP CO 2 (HPCD) combined with nisin. The authors suggest that HPCD promotes the penetration of nisin into the spores by damaging their coat and cortex.…”
Section: Discussionsupporting
confidence: 56%
“…One of such prominent bacteriocins (E234) unspotted in health problems is nisin, an oligopeptide produced by certain strains of Lactococcus ( Cotter et al, 2012 ; Rao et al, 2016 ). Nisin is a cationic peptide composed of 34 amino acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…The straightforward solution is to use combinational methods to improve the bacteria inactivation efficiency (i.e., garlic extracts, CO 2 , pressure, thermal stress), which all showed an improvement in nisin-mediated biopreservation ( Lee and Kaletunç, 2010 ; Al-Holy et al, 2012 ; Chandrasekaran et al, 2013 ; Pinilla and Brandelli, 2016 ; Rao et al, 2016 ). However, since the bacteriocins can lose their antimicrobial activity due to environmental factors such as pH, temperature, or food composition ( Zhou et al, 2014 ) additional encapsulation and use of nanostructures as carriers are advantageous ( Lopes and Brandelli, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nisin is produced by certain strains of Lactococcus spp. and is effective against broad spectrum of gram-positive bacteria (Gharsallaoui et al., 2016; Rao et al., 2016; Campion et al., 2017). It incorporates itself in the cell membrane by binding to essential precursors for cell wall biosynthesis, which ultimately leads to the formation of pores, loss of solutes in bacteria, and subsequent cell death (Wiedemann et al., 2004; Novickij et al., 2018b).…”
Section: Introductionmentioning
confidence: 99%